2019
DOI: 10.1523/jneurosci.2876-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

The p75 Neurotrophin Receptor Is an Essential Mediator of Impairments in Hippocampal-Dependent Associative Plasticity and Memory Induced by Sleep Deprivation

Abstract: Sleep deprivation (SD) interferes with hippocampal structural and functional plasticity, formation of long-term memory and cognitive function. The molecular mechanisms underlying these effects are incompletely understood. Here, we show that SD impaired synaptic tagging and capture and behavioral tagging, two major mechanisms of associative learning and memory. Strikingly, mutant male mice lacking the p75 neurotrophin receptor (p75 NTR ) were resistant to the detrimental effects of SD on hippocampal plasticity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 89 publications
(132 reference statements)
5
75
0
Order By: Relevance
“…While a previous work established that circadian rhythm can regulate the transcriptional activation of p75NTR in the nervous system and peripheral tissues, indicating its role in maintenance of the circadian clock and metabolic gene oscillation, the association between p75NTR and sleep deprivation in synaptic plasticity and cognitive decline was not investigated (12). In their paper, Wong et al (8) showed that sleep deprivation could impair crucial synaptic processes that are necessary for associative learning and memory. Furthermore, they found that sleep deprivation modulates the RhoA-ROCK2 and cAMP-PKA-LIMK1-cofilin pathways via p75NTR.…”
Section: P75ntr Is a Key Molecular Signal For Synaptic Plasticity Durmentioning
confidence: 98%
See 1 more Smart Citation
“…While a previous work established that circadian rhythm can regulate the transcriptional activation of p75NTR in the nervous system and peripheral tissues, indicating its role in maintenance of the circadian clock and metabolic gene oscillation, the association between p75NTR and sleep deprivation in synaptic plasticity and cognitive decline was not investigated (12). In their paper, Wong et al (8) showed that sleep deprivation could impair crucial synaptic processes that are necessary for associative learning and memory. Furthermore, they found that sleep deprivation modulates the RhoA-ROCK2 and cAMP-PKA-LIMK1-cofilin pathways via p75NTR.…”
Section: P75ntr Is a Key Molecular Signal For Synaptic Plasticity Durmentioning
confidence: 98%
“…Notably, previous studies investigated the molecular underpinnings and found that sleep deprivation selectively impaired cAMP/PKA-dependent forms of synaptic plasticity in the hippocampus to reduce cAMP signaling and increase phosphodiesterase-4 activity, which degrades cAMP (15). One key finding in the recently published paper by Wong et al (8) is that p75NTR confers a protective effect on late LTP deficits induced by sleep deprivation. Sleep deficiency can cause LTP deficits, specifically STC deficits.…”
Section: P75ntr Confers a Protective Effect On Late Ltpmentioning
confidence: 99%
“…The negative impact of SD on hippocampal function is at least partly caused by increased phosphodiesterase (PDE) activity and related suppression of cAMP signaling (Havekes et al, ; Havekes, Park, Tolentino, et al, ; Vecsey et al, ). Because cGMP and cAMP signaling potentially target the same downstream signaling molecules known to be affected by SD (i.e., CREB (Wong, Tann, Ibanez, & Sajikumar, ), LIMK1‐cofilin (Havekes, Park, Tudor, et al, ; Wong et al, ; Zulauf et al, )), cGMP signaling may also be a relevant therapeutic target in this respect. While disrupting effects of SD have been reported for a variety of hippocampal tasks (Havekes & Abel, ; Havekes, Meerlo, & Abel, ), its impact on pattern separation remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Because cGMP and cAMP signaling potentially target the same downstream signaling molecules known to be affected by SD (i.e., CREB (Wong et al, ), LIMK1‐cofilin (Havekes, Park, Tudor, et al, )), as a next step we targeted cGMP signaling using the PDE5 inhibitor vardenafil. Vardenafil has previously shown to increase cGMP in the hippocampus and improve the memory function in rodents (Akkerman et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation